Ureteropelvic junction obstruction caused by Fibroepithelial polyps in children - Knoblich, Maria (2017)
Introduction Fibroepithelial polyps are extremely rare benign tumors arising from mesodermal tissue in the ureteral wall in children, that can cause ureteropelvic junction obstruction.Case reportIn this report, we present an 11‐year‐old boy complaining of left intermitent lumbar pain related with ipsilateral hydronephrosis. Surgical exploration revealed several endoluminal polyps located at the ureteropelvic junction, obstructing the lumen of the ureter.DiscussionStandard treatment consists in resection of the affected ureteral segment followed by open or laparoscopic dismembered pyeloplasty. The prognosis is excellent.